2015
DOI: 10.4238/2015.july.31.11
|View full text |Cite
|
Sign up to set email alerts
|

Study on the correlation between the expression of Ki67 and FasL and prognosis of cervical carcinoma

Abstract: ABSTRACT. This study aimed to investigate the correlation between the expression of Ki67 and FasL and prognosis of cervical carcinoma and to explore the biological processes and signal pathways related to cervical carcinoma. Cervical carcinoma tissue specimens from 200 patients and normal tissue specimens adjacent to lesions from 30 cases were collected in this study. Ki67 and FasL proteins in these specimens were detected by immunohistochemical methods. A series of statistical methods were carried out to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In the present study, the combination of FA-chitosan/mIP-10 and FC vaccine significantly reduced the number of Ki67 + tumor cells but increased the number of apoptotic cells in the tumor tissues which was consistent with the previous reports 31, 32, 33. These data suggest that Th1 and CTL cells induced by combination therapy inhibit the proliferation of tumor cells and trigger apoptosis by direct cell-cell contact or indirectly by soluble mediators.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the combination of FA-chitosan/mIP-10 and FC vaccine significantly reduced the number of Ki67 + tumor cells but increased the number of apoptotic cells in the tumor tissues which was consistent with the previous reports 31, 32, 33. These data suggest that Th1 and CTL cells induced by combination therapy inhibit the proliferation of tumor cells and trigger apoptosis by direct cell-cell contact or indirectly by soluble mediators.…”
Section: Discussionsupporting
confidence: 93%
“…12,13 According to previous studies, high KI67 expression in CC is related to the size of tumors, progression of tumors, and lymph node metastases. 14 Gene set enrichment analysis (GSEA) analysis showed that biological pathways, such as cell cycle, oocyte meiosis, RNA degradation, and fatty acid metabolism and biosynthesis were enriched in cluster 3 (Figure 2E). Meanwhile, cluster 3 was found to have higher levels of G 2 /M signatures, suggesting high proliferative activity.…”
Section: Single-cell Transcriptomics Reveal Intra-tumoral Heterogeneity In CC Cellsmentioning
confidence: 99%
“…Ki67 is a nuclear protein, and its expression level is strongly associated with tumor cell proliferation and growth and is widely used in routine pathological investigations as a proliferation marker. Clinically, Ki67 expression is significantly higher in malignant tissues with poorly differentiated tumor cells than in normal tissue [21,22]. In cervical cancer, the expression of Ki67 is closely related to the occurrence and development of cervical carcinoma [22].…”
Section: Patientmentioning
confidence: 99%
“…Clinically, Ki67 expression is significantly higher in malignant tissues with poorly differentiated tumor cells than in normal tissue [21,22]. In cervical cancer, the expression of Ki67 is closely related to the occurrence and development of cervical carcinoma [22]. Therefore, the expression of SCCA and Ki67 levels were evaluated in our study for prognostic research.…”
Section: Patientmentioning
confidence: 99%